Women's Choice to Deliver at Home: Understanding the Psychosocial and Cultural Factors Influencing Birthing Choices for Unskilled Home Delivery among Women in Southwestern Uganda. (3rd June 2020) - Atukunda, Esther C.; Mugyenyi, Godfrey R.; Obua, Celestino; Musiimenta, Angella; Agaba, Edgar; Najjuma, Josephine N.; Ware, Norma C.; Matthews, Lynn T.
Abstract : Background . Utilization of perinatal services in Uganda remains low, with correspondingly high rates of unskilled home deliveries, which can be life-threatening. We explored psychosocial and cultural factors influencing birthing choices for unskilled home delivery among postpartum women in rural southwestern Uganda. Methods . We conducted in-depth qualitative face-to-face interviews with 30 purposively selected women between December 2018 and March 2019 to include adult women who delivered from their homes and health facility within the past three months. Women were recruited from 10 villages within 20 km from a referral hospital. Using the constructs of the Health Utilization Model (HUM), interview topics were developed. Interviews were conducted and digitally recorded in a private setting by a native speaker to elicit choices and experiences during pregnancy and childbirth. Translated transcripts were generated and coded. Coded data were iteratively reviewed and sorted to derive categories using inductive content analytic approach. Results . Eighteen women (60%) preferred to deliver from home. Women's referent birth location was largely intentional. Overall, the data suggest women choose home delivery (1) because of their financial dependency and expectation for a " natural " and normal childbirth, affecting their ability and need to seek skilled facility delivery; (2) as a means of controlling their own birth processes; (3) out of dissatisfaction with facility-based care; (4) out of strong belief in fate regarding birth outcomes; (5) because they have access to alternative sources of birthing help within their communities, perceived as " affordable, " " supportive, " and " convenient "; and (6) as a result of existing gender and traditional norms that limit their ability and freedom to make family or health decisions as women. Conclusion . Women's psychosocial and cultural understandings of pregnancy and child birth, their established traditions, birth expectations, and perceptions of control, need, and quality of maternity care at a particular birthing location influenced their past and future decisions to pursue home delivery. Interventions to address barriers to healthcare utilization through a multipronged approach could help to debunk misconceptions, increase perceived need, and motivate women to seek facility delivery.